2021
DOI: 10.1186/s12874-021-01215-y
|View full text |Cite
|
Sign up to set email alerts
|

The STS case study: an analysis method for longitudinal qualitative research for implementation science

Abstract: Background Ethnographic approaches offer a method and a way of thinking about implementation. This manuscript applies a specific case study method to describe the impact of the longitudinal interplay between implementation stakeholders. Growing out of science and technology studies (STS) and drawing on the latent archaeological sensibilities implied by ethnographic methods, the STS case-study is a tool for implementors to use when a piece of material culture is an essential component of an inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…These dual challenges-of implementing routine screening in primary care and developing HIT that enhances rather than detracts from clinician and patient experience-underline the importance of sociotechnical frameworks for informing intervention design. Our study is part of a growing literature employing these concepts to inform intervention development and HIT implementation in healthcare settings [50,51,88,90,91]. This and prior studies show how understanding clinician experience and organizational context provides insight into unintended consequences of HIT implementation, including "alert fatigue," cumbersome tools that exacerbate time limitations, and concerns that documentation does not inform patient care.…”
Section: Plos Onementioning
confidence: 88%
See 1 more Smart Citation
“…These dual challenges-of implementing routine screening in primary care and developing HIT that enhances rather than detracts from clinician and patient experience-underline the importance of sociotechnical frameworks for informing intervention design. Our study is part of a growing literature employing these concepts to inform intervention development and HIT implementation in healthcare settings [50,51,88,90,91]. This and prior studies show how understanding clinician experience and organizational context provides insight into unintended consequences of HIT implementation, including "alert fatigue," cumbersome tools that exacerbate time limitations, and concerns that documentation does not inform patient care.…”
Section: Plos Onementioning
confidence: 88%
“…"Sociotechnical" approaches can complement implementation science concepts by increasing our understanding of the dynamic and complex nature of healthcare systems [47][48][49][50][51].…”
Section: Using Qualitative Methods To Inform Intervention Developmentmentioning
confidence: 99%
“…The main advantage of a case study was that researchers might use case studies for mainly unexplored or underexamined topics for which little or scarce empirical evidence existed (Çakar & Aykol, 2021). Another advantage was that researchers and implementors might engage with the complex implementation process and inform data collection by tracking changes over time (Van Tiem et al, 2021).…”
Section: Case Study As Second Methods In Chinese Researchmentioning
confidence: 99%
“…The goal of the study was to identify barriers and facilitators to successful integration of tobacco-free workplace policy and cessation practices into a substance use treatment center. The current study was based on an ethnographic approach and uses a case study design, which is considered an efficient way to present qualitative ethnographic findings [ 33 , 34 ]. Case study design has been found to be particularly useful in implementation research, as it allows for an in-depth analysis of complex interventions in combination with a participatory approach in a real-life context [ 35 38 ].…”
Section: Introductionmentioning
confidence: 99%